2015
DOI: 10.1161/strokeaha.114.007950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seasonal and Monthly Variation in Weather and Air Pollution Factors on Stroke Incidence in Seoul, Korea

Abstract: Background and Purpose-The purpose of the present study was to determine whether seasonal and monthly variations in stroke incidence exist and whether they are related to meteorologic and air pollution parameters under similar weather and environmental conditions in selected areas of Seongdong district, Seoul, South Korea. Methods-From January 1, 2004, to December 31, 2013, 3001 consecutive stroke events were registered in residents of selected areas of Seongdong district, Seoul, South Korea. The authors calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 45 publications
(43 reference statements)
5
60
1
Order By: Relevance
“…The number of strokes increased with temperature and daily temperature range, associations with low pressure and falling pressure were observed which is in line with our observations since we also reported that stroke cases are predicted by daily lowest - and also highest - air pressure and highest air temperature. Han et al recently demonstrated distinct patterns of seasonal and monthly variation in the stroke incidence and its subtypes through consideration of the meteorological and air pollution parameters in nine year term in Seoul, South Korea (3). They found that the mean temperature was positively correlated with stroke which is in line with our findings (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of strokes increased with temperature and daily temperature range, associations with low pressure and falling pressure were observed which is in line with our observations since we also reported that stroke cases are predicted by daily lowest - and also highest - air pressure and highest air temperature. Han et al recently demonstrated distinct patterns of seasonal and monthly variation in the stroke incidence and its subtypes through consideration of the meteorological and air pollution parameters in nine year term in Seoul, South Korea (3). They found that the mean temperature was positively correlated with stroke which is in line with our findings (3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circadian variation has been also shown to have an important effect (2). Recently, more attention has been oriented toward the effect of weather conditions on stroke admissions (3-5). However, evidence of the impact of air temperature and pressure and the extreme weather conditions (tropical storms, hurricanes) on cerebrovascular morbidity is still quite limited and controversial.…”
mentioning
confidence: 99%
“…Constantly informing the public of the need to seek medical help promptly after stroke onset and using an ambulance and direct transportation to the hospital. Also it is necessary to have more effective in-hospital organization in order to improve availability of effective acute treatment options to stroke patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies stroke occurence was more frequent on weekdays than on weekends (6), and usually on Mondays (7,9,14). Some studies found no difference in the frequency of occuring of all stroke types by days of the week (2), some of them found no difference for ICH and SAH (4, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation